Molecular and biochemical mechanisms involved in the toxicity of a marine cyanobacteria compound on cancer cell lines - Melissa Sofia Figueiredo Couto (2016)
In recent years marine biotechnology has revealed a crucial role in the future of bioindustry. Among the many marine resources, cyanobacteria have shown great potential in the production of bioactive compounds with diverse applicability. The pharmacological potential of these organisms has been one of the most explored areas in particular its antibacterial, antifungal and anticancer potential. This work was based on the assessment of potential anticancer compound E13010 F 5.4 isolated from marine cyanobacteria strain Synechocystis salina LEGE 06099. Thus the aim of this work was to explore molecular and biochemical mechanisms underlying the bioactivity detected in human cancer cells, specifically in lines RKO colon carcinoma and HT-29. The isolation of the compound was performed from biomass obtained by large-scale culture. To obtain the compound fractionation was carried and confirmation and isolation performed by Nuclear Magnetic Resonance (NMR), Thin Layer Chromatography (TLC) and High-Performance Liquid Chromatography (HPLC). Cell viability assays were performed based on reduction of 3- (4,5-dimetiltiaziol-2-yl) -2,5-diphenyltetrazolium bromide (MTT) to assess the cytotoxic potential of the compound. From the battery of cell lines RKO (colon carcinoma), HT-29 (colorectal adenocarcinoma), MG-63 (osteosarcoma) and T47D (breast carcinoma) the cell lines RKO and HT-29 were selected for elucidation of mechanisms of cytotoxicity. For the elucidation of the mechanisms involved in cytotoxicity the cell lines RKO and HT29 were exposed to the compound. A genomic approach based in the mRNA expression of genes involved in apoptosis and cell cycle by Real-Time PCR and a proteomic approach based on the separation of proteins by two-dimensional electrophoresis (2DGE) was performed. For mRNA expression were selected the genes RPL8, HPRT1, VDAC, SHMT2, CCNE, CCNB1, P21CIP, BCL-2 and BAD and for proteomics isoelectric focussing between 3 – 10 and molecular weight of 19 – 117 kDa separated by polyacrylamide gels (2DGE). The MTT results confirmed the reduction of the cell viability. The RT-PCR results for the expression of genes studied were not yet fully elucidative. For the cell line RKO there was a significant reduction in the expression of the gene P21CIP, and a tendency for reduction in the BAD gene expression and for increased expression of gene CCNB1, pointing to an effort for cell proliferation. In HT-29 cell line, there was a tendency for increase in the expression of P21CIP and BAD, which may explain the reduction in cell viability. The 2DGE results indicate proteomic patterns with differentially altered spots in the treated and control cells with both qualitative and quantitative differences, and differences in response between the RKO and HT-29 cell lines.